The Critical Role of CT Imaging in Detecting Acute Neurological Complications of Eclampsia: A Case Series - Ayu Angelina Ronosulistyo; Zulvayanti Zulvayanti; Dini Hidayat; Windi Nurdiawan; Hadi Susiarno; Dini Pusianawati; Vyanda Sri Weningtyas (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
AbstractIntroduction: An intracranial hemorrhage (ICH) is a rare condition but potentially life-threatening event, especially in pregnancy, and could happen in patients with eclampsia. At Hasan Sadikin General Hospital (RSHS), several eclampsia cases are admitted annually, some with worsening neurological conditions. Neuroimaging using CT-Scan is indicated in patients with seizures, decreased consciousness, or visual disturbances to detect intracranial pathology.  Case: We reported three cases of maternal eclampsia, two patients' chief complaint was seizures, but all of our patients were unconscious. All of our patients had a previous history of pre-eclampsia in the last pregnancy. All of our patients performed a CT scan performed in postpartum patients as a neurologic examination. All of our patients have worse outcomes. The Medical and Health Research Ethics Committee of the Faculty of Medicine, Padjajaran University with Ref no: DP.04.03/D/XIV.6.5/71/2025.Conclusion: Neuroimaging in patients with seizure-induced worsening of the condition has an important role in identifying other abnormalities, specifically intracranial hemorrhage. In this study, we conclude that patients with seizures in pregnancy should be screened with neuroimaging (computed tomography scan) to rule out central nervous system pathology, thereby improving the patient's condition and reducing maternal mortality.Keywords: CT scan, Convulsion, Eclampsia, Pregnancy Peran Kritis Pencitraan CT dalam Mendeteksi Komplikasi Neurologis Akut pada Eklampsia: Seri KasusAbstrakPendahuluan: Perdarahan intrakranial (PIK) merupakan kondisi langka namun berpotensi mengancam jiwa, terutama pada kehamilan, dan dapat terjadi pada pasien eklampsia. Neuroimaging menggunakan CT-Scan berperan dalam deteksi dini perburukan kondisi pasien dengan penurunan kesadaran.Kasus: Penelitian ini melaporkan tiga kasus eklampsia maternal, keluhan utama dua pasien adalah kejang, namun semua pasien pada penelitian ini tidak sadar. Semua pasien memiliki riwayat preeklampsia sebelumnya pada kehamilan terakhir. Semua pasien melakukan CT scan sebagai pemeriksaan neurologis. Semua pasien memiliki hasil yang lebih buruk. Komite Etik Penelitian Kedokteran dan Kesehatan Fakultas Kedokteran Universitas Padjadjaran dengan Ref no: DP.04.03/D/XIV.6.5/71/2025.Kesimpulan: Neuroimaging pada pasien dengan kondisi yang memburuk akibat kejang memiliki peran penting dalam mengidentifikasi kelainan lain, khususnya perdarahan intrakranial. Dalam penelitian ini, peneliti menyimpulkan bahwa pasien dengan kejang selama kehamilan harus diskrining dengan neuroimaging (pemindaian tomografi terkomputasi) untuk menyingkirkan patologi sistem saraf pusat sehingga memperbaiki kondisi pasien dan mengurangi angka kematian ibu.Kata kunci: CT scan, Eklampsia, Kehamilan, Kejang